# 5-2(4-2x)=21Can you help me find x ???

beckden | High School Teacher | (Level 1) Educator

Posted on

5-2(4-2x)=21   First we distribute

5-(2(4)-2(2x))=21    Continue distributing

5-(8-4x) = 21    Change the sign of everything we are subtracting

5 - 8 + 4x = 21  Simplify

-3 + 4x = 21    Add 3 to both sides

-3 + 3 + 4x = 21 + 3 simplify

4x = 24   Divide by 4

x = 6  Our answer.   Check 5-2(4-2(6))=5-2(4-12)=5-2(-8)=5-(-16)=5+16=21

givingiswinning | Student, Grade 10 | (Level 1) Valedictorian

Posted on

5-2(4-2x)=21

distribute -2

5 - 8 + 4x =21

combine like terms

-3 + 4x = 21

4x = 21 + 3

combine like terms

4x = 24

now divide by 4

x = 6

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

5-2(4-2x)=21

distribute the 2

5 - 8 + 4x =21

combine like terms:

-3 + 4x = 21

4x = 21 + 3

combine like terms again:

4x = 24

now divide by 4x

x = 6

jess1999 | Student, Grade 9 | (Level 1) Valedictorian

Posted on

5 - 2 ( 4 - 2x ) = 21

To solve this equation , first distribute the 2

By distributing the 2 , you should get

5 - 8 + 4x = 21 now combine the like terms ( which is 5 and -8 )

By combining the like terms , you should get

-3 + 4x = 21 now add 3 on both sides

By adding 3 on both sides , you should get

4x = 24 now divide both sides by 4 .

By dividing both sides by 4 , you should get

katieruellia | Student, Grade 9 | eNotes Newbie

Posted on

@hockeypuck124

Ummm... I think something went wrong in your equation. @beckden did it right because in your first step you combined the terms from

5-2(4-x)=21

to

3(4-2x)=21

You're not supposed to subtract two terms that are not of the same type i.e you're should do the multiplying part first:)

Hope this helps:\$

hockeypuck124 | Student, Grade 10 | (Level 2) eNoter

Posted on

I didnt get the same answer as above, but I'm doing this now in my math class and this is what I did.

5-2(4-2x)=21

First combine like terms. 3(4-2x)=21.

Next divide by 3 on both sides. (4-2x)=7

Then to get rid of the parenthesis you use square root. 4-2x= + or - the square root of 7.

Then subtract by 4 on both sides. -2x=-4 + or - the square root of 7.

Last divide by -2 on both sides. x=2 + or - the square root of 7.